Development of Cancer Immunotherapeutics Targeting Complement Regulatory Protein CD55 - Bradley, Richard Grayson (2007)
CD55 is one of the complement regulatory/inhibitory proteins and is over-expressed on a wide range of solid tumours. CD55 is also known to be deposited within tumour stroma and is secreted in an active soluble form, mediated by matrix metalloproteinase-7. The complement cascade forms part of the innate immune system and culminates in cell lysis of targeted cells. As a complement regulatory protein, the primary function of CD55 is to accelerate the decay of complement components preventing formation of the membrane attack complex.